PERFORMING ISLAMIC EDUCATION WITH A HUMANISTIC APPROACH TO FORM A RELIGIOUS YOUNG GENERATION AT YOUTH FORCE MUHAMMADIYAH IN UMBULHARJO SUB-DISTRICT OF YOGYAKARTA - Nur Faizah (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
Religious youths are unimpeachable and light for their parents because of their good behavior, obedience, and devotion to worship. Parents must prepare as early as possible to make their children religious youths through education and other. However, world life is full of attractive offers that can demolish conditions being constructed thoroughly because the learning approach and education are insufficient. The researcher pays attention to teenagers in PCM Umbulharjo who seem sluggish, like a lack of religious assembly to recite and activities related to religion. A researcher intends to re-encourage using a humanistic approach. This study used the qualitative method by collecting data and compelling information through observation, interviews, and existing documents. The target for conducting this research was the youth force Muhammadiyah in Umbulharjo sub-district, which discovered a new approach to solving contemporary issues.